Knitting Two Together (K2tog), "If You Meet Another Knitter You Always Have a Friend". (2nd July 2020) - Court, Kate
Abstract: Only one person at a time works on a piece of knitting and it is often a solitary activity. However, it can also be very social. For some, the opportunity to interact online and in-person with other knitters is a significant motivation for undertaking the activity. Knitters interviewed as part of this qualitative research reported three core inter-related benefits of sharing their knitting with other people: technical support; feeling part of a community; and forming meaningful friendships. This article makes an original contribution by exploring the nature of the benefits of knitting as a way of connecting with others. It follows that friendships can spring from leisure activities, as participants may be likely to have some similar interests. The article speculates that undertaking a shared and tangible activity seems to offer powerful benefits to ease and facilitate meaningful social interactions. Women were the focus of this study and it is suggested that the opportunity to experience these interactions with other women was core to their experience. This empirical research project used a grounded theory approach, involving several stages of data collection and analysis. This article is primarily based on the final stage, consisting of in depth interviews with women knitters.